Molecular analysis of occult hepatitis B infection among Iranian HIV-positive patients. (July 2016) - Mohraz, Minoo; Jafari, Rezvaneh; Poortahmasebi, Vahdat; Sadeghi, Ahmadreza; Hajabdolbaghi, Mahboobeh; Rasoolinejad, Mehrnaz; Forooghi, Maryam; Norouzi, Mehdi; Poorebrahim, Mansour; Khamseh, Azam; Karkhaneh, Masoud; Alavian, Seyed Moayed; et al.
Aim: The aims of this study were to find out the prevalence of occult hepatitis B infection (OBI) in HIV-1 patients, as well as to analyze the mutational patterns of OBI-positive individuals.Materials & methods: 172 HBsAg-negative, HIV-1-positive patients were selected according to data extracted from questionnaires. HBV serologic and molecular assays were performed. An extensive mutational analysis was applied using direct sequencing on HBsAg.Results: Thirty-one samples (18%) were OBI positive. Among 24 available OBI-positive samples, 17 (71%) contained at least one mutation only within 'a' determinant region of HBsAg. A stretch of mutations was found between amino acid positions 121 and 136. The physicochemical properties of individual amino acid substitutions and their potential impacts on 3D structure of 'a' determinant mutants were also determined.Conclusion: HBV serologic assays are not reliable markers to exclude occult HBV infection in HIV-positive patients.